Evaluation of fatigue and quality of life of colorectal cancer patients in chemotherapy - Rafaela Costa Silva; Michele Carla Gonçalves; Amanda Silva Mendes; Mariana Rosa Ribeiro Cardoso; Adriana Cristina Nicolussi (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To evaluate fatigue and health-related quality of life of colorectal cancer patients undergoing chemotherapy. Method: Descriptive study conducted with 69 patients between January and September/2019 in a public hospital in Minas Gerais. Instruments used: sociodemographic and clinical questionnaire, Quality of Life Questionnaire-Core30 and Piper Fatigue Scale, analyzed according to measures of frequency, mean and standard deviation by the software PSPP. Results: Most patients were women over 60 years old, married, retired and housewives, with an average level of education. The scores of general health status, social, physical, emotional and role functioning were considered satisfactory (means 50 to 70), cognitive function was good (mean higher than 70); the most prevalent symptoms were loss of appetite, fatigue, pain and insomnia. As for fatigue, all dimensions had a mean value <4, considered mild fatigue. Conclusion: Quality of life had satisfactory scores and fatigue was classified as mild in patients undergoing chemotherapy.